Strengthening Halal Industry MSMEs through Islamic Financing: A Triple Helix Ecosystem Perspective - Desy Arum Sunarta; Lestari Daswan; Riski Apriliani; Nurfadilah Maulana S; Amalia S Tapparang (Institut Muslim Cendekia, 2026)
Islamic financing has become a critical mechanism for strengthening halal micro, small, and medium enterprises (MSMEs), particularly within the expanding Islamic economic landscape. However, prior studies tend to examine Islamic financing, halal MSMEs, and institutional collaboration separately, leaving a gap in understanding their integrated role within a unified ecosystem. This study addresses this gap by analyzing the role of Islamic financing in supporting halal MSMEs through the Triple Helix framework, which highlights the interaction among government, industry, and academia. Employing a qualitative systematic literature review, this study synthesizes evidence from peer-reviewed research on Islamic finance, halal industry development, and collaborative governance. The findings demonstrate that Islamic financing contributes to MSME performance not only through improved access to ethical financial resources but also through the synergy of regulatory support, financial innovation, and knowledge development. Government ensures regulatory clarity and infrastructure, Islamic financial institutions provide sharia-compliant and digital financing solutions, while academia enhances financial literacy and innovation capacity. This study argues that the effectiveness of Islamic financing is contingent upon the integration of these institutional roles within a cohesive ecosystem. The contribution of this research lies in offering an integrative conceptual framework that links Islamic financing with the Triple Helix model, providing strategic insights for strengthening sustainable halal MSME development and advancing inclusive Islamic economic systems.